3D modeling of archaeological pieces using photogrammetry (Damascus University Journal for engineering sciences, 2021)
Close range photogrammetry has become one of the most effective ways for digital documentation of culture heritage, especially with the popularity of digital cameras and related software. Nevertheless, this risks yielding erroneous results if topographic experts don’t interfere in determining and assessing the accuracy and the precision of data and operations. This article approaches the procedure of modeling some of the national museum of Damascus using the close range photogrammetry technique. Some principles of digital photogrammetry and computer vision are highlighted .The introduced model is a surface type one which consists of a mesh of irregular triangulation built on a base of dense point cloud resulted in a photogrammetric ways. The main steps of modeling procedure are elaborated such as camera calibration and the planning of photo acquisition session. Final model is verified according to the indices of the accuracy of archeological modeling.
Keywords: Documentation, Close range photogrammetry, Image matching, Modeling, Triangulation.